Integration of PAI with Environmental Preservation: Building Ecological Piety for Students at School - Lutfi, Saiful; Hamdanah, Hamdanah; Normuslim, Normuslim (International Journal of Humanities, Education, and Social Sciences, 2025)
The integration of Islamic Religious Education (PAI) with environmental conservation to build ecological piety among students is important to preserve nature in the future. Therefore, education based on Islamic values collaborated with natural knowledge is expected to increase environmental awareness among the younger generation. In accordance with the existing statement, the purpose of this study is to examine how the integration of PAI can shape the character of students who care about the environment. This research uses a descriptive qualitative approach and literature study to explore relevant literature so as to obtain research results that show that religious education integrated with environmental preservation can increase students' ecological awareness. The research subjects were teachers and students of MTsN 1 Palangka Raya, while the data collection techniques used observation, interviews and documentation. The results showed that in addition, programs such as Adiwiyata School in MTsN 1 Palangka Raya have proven effective in shaping a culture of environmental care in schools. Although there are challenges in implementing the curriculum, innovative efforts are needed to overcome these obstacles. This research is expected to contribute in developing more effective learning strategies in terms of environmental conservation.